Evolution of a dextral lineage by left–right reversal in Cristataria (Gastropoda, Pulmonata, Clausiliidae). (13th March 2019) - Páll‐Gergely, Barna; Szekeres, Miklós; Fehér, Zoltán; Asami, Takahiro; Harl, Josef
Abstract: It has long been debated whether mirror image‐like similarity in shell morphology between enantiomorphic pairs of dextral and sinistral taxa represents their sister relationship, or each of them is closer related to other congeners with the same coiling direction. The obligate rock‐dwelling genus Cristataria Vest, 1867 of the eastern Mediterranean region belongs to the Alopiinae subfamily of door snails (Clausiliidae). Cristataria and a few other genera of this subfamily include enantiomorphic pairs that are conchologically very similar to each other. Dextral C. colbeauiana (Pfeiffer, 1861) and its sinistral counterpart of such an enantiomorphic pair occur nearby one another in southern Turkey. However, the latter has been classified either as the sinistral subspecies C. colbeauiana inversa Szekeres, 1998 or as a form of sinistral C. leprevieri (Pallary, 1922). To examine the phylogenetic relationship of this enantiomorphic pair, we carried out molecular phylogenetic analysis of all the Turkish and two other Cristataria taxa based on both mitochondrial and nuclear DNA markers. Our results show that dextral C. colbeauiana and its sinistral counterpart are closest related to one another. This supports the classification of this enantiomorphic pair as dextral C. colbeauiana colbeauiana and sinistral C. colbeauiana inversa . Our results also reveal that these taxa and C. intersita Németh & Szekeres, 1995, sharing a characteristic collar behind the aperture of the shell, represent a monophyletic lineage. By contrast, the Cristataria species of non‐collared shells belong to another clade. Abstract : It has long been debated whether mirror image‐like enantiomorphic taxa in a genus have sister relationship, or each of them is closer related to congeneric members of their own coiling direction. The predominantly sinistral rock‐dwelling genus Cristataria of the eastern Mediterranean region contains only a single dextral taxon. For interpreting its status within the genus, two contrasting morphology‐based hypotheses have been proposed, which we tested by molecular phylogenetic analysis.